Training for dementia care and support in rural and remote Australia: appraisals from a nationwide workforce survey - John A. Woods; Jessica Valentine; Kira Gusterson; Kathryn W. Fitzgerald; Katrina P. Fyfe; Myles Clarkson Fletcher; Mohammad Hamiduzzaman; Pascale Dettwiller; Anthony B. Fallon; Clare Dal Bon; Sarah E. Miles; Jo-Anne W. Rayner; et al. (BMC Geriatrics)
Abstract Background Dementia is a growing challenge to health and aged care worldwide and is the leading cause of disease burden in older Australians. High-quality person-centred care of people with dementia and support for their family caregivers require a trained multidisciplinary health and aged care workforce. Compared with major cities in Australia, rural and remote areas encounter greater challenges in workforce recruitment and retention. Moreover, these areas have distinctive distance-related barriers to workforce training and a higher proportion of aged and First Nations people at elevated risk of developing dementia. We designed and distributed a survey to investigate the perspectives on training among rural and remote health and aged care workers providing dementia care in diverse occupations and settings. Methods After piloting, the online survey was promoted to rural and remote organisations and professional networks nationwide. The instrument included multiple-choice and ordered-scale items on respondents’ dementia care self-rating and appraisal of their current workplace dementia care training, as well as items categorising their demographic characteristics, main work role, main workplace setting, and geographical site. Analysis incorporated description of respondent characteristics and estimation along with graphical presentation of response proportions for ordered-scale items, with differences among key respondent subgroups (i.e., workplace setting, remoteness, and main role) investigated using crude and multivariable robust Poisson regression models. Results There were 558 respondents from residential aged care, community/primary care and hospital settings across all Australian states and territories. The majority (61.7%) were from degree-requiring health professional/management positions, and 27.4% were certificate-requiring workers (predominantly personal care assistants and enrolled nurses). A majority considered that the dementia care provided in their current workplace was inadequate overall and specifically in relation to First Nations and culturally and linguistically diverse clients. Respondents noted organisational resource limitations impeding workers’ participation in training, and insufficient opportunities for input into determining priorities for training content and delivery. Hospital/acute care-based workers had the least favourable self-ratings and represented the highest proportion of respondents reporting shortcomings of training. Conclusions Health and aged care workers in rural and remote Australia perceive substantial shortcomings in the dementia care training provided by their workplace.